A sampling strategy for longitudinal and cross-sectional analyses using a large national claims database - McMurry, Timothy L.; Lobo, Jennifer M.; Kim, Soyoun; Kang, Hyojung; Sohn, Min-Woong (Frontiers in Public Health, 2024)
Importance: The United States (US) Medicare claims files are valuable sources of national healthcare utilization data with over 45 million beneficiaries each year. Due to their massive sizes and costs involved in obtaining the data, a method of randomly drawing a representative sample for retrospective cohort studies with multi-year follow-up is not well documented.Objective: To present a method to construct longitudinal patient samples from Medicare claims files that are representative of Medicare populations each year.Design: Retrospective cohort and cross-sectional designs.Participants: US Medicare beneficiaries with diabetes over a 10-year period.Methods: Medicare Master Beneficiary Summary Files were used to identify eligible patients for each year in over a 10-year period. We targeted a sample of 900,000 patients per year. The first year's sample is stratified by county and race/ethnicity (white vs minority), and targeted at least 250 patients in each stratum with the remaining sample allocated proportional to county population size with oversampling of minorities. Patients who were alive, did not move between counties, and stayed enrolled in Medicare fee-for-service (FFS) were retained in the sample for subsequent years. Non-retained patients (those who died or were dropped from Medicare) were replaced with a sample of patients in their first year of Medicare FFS eligibility or patients who moved into a sampled county during the previous year.The resulting sample contains an average of 899,266±408 patients each year over the 10-year study period and closely matches population demographics and chronic conditions. For all years in the sample, the weighted average sample age and the population average age differ by < 0.01 years; the proportion white is within 0.01%; and the proportion female is within 0.08%. Rates of 21 comorbidities estimated from the samples for all 10 years were within 0.12% of the population rates. Longitudinal cohorts based on samples also closely resembled the cohorts based on populations remaining after 5-year and 10-year follow-up.This sampling strategy can be easily adapted to other projects that require random samples of Medicare beneficiaries or other national claims files for longitudinal follow-up with possible oversampling of sub-populations.